THE STUDENTS' ABILITY IN USING TREE DIAGRAMS AT THE THIRD SEMESTER OF ENGLISH STUDY PROGRAM ISLAMIC UNIVERSITY OF INDRAGIRI - Jena Mardhika; Melda Yeni; Samsul Amri (J-Shelves of Indragiri (JSI), 2025)
Syntax is a sub-discipline of linguistics that studies the relationship between words in speech, including phrase structure, clause structure, and sentence structure in a language. Tree diagrams are a great method of understanding syntax. The purpose of this study is to ascertain the third semester English Study Program students at Indragiri Islamic University proficiency in understanding tree diagrams. This kind of study is descriptive quantitative. Twenty-one students made up the study's total population and sample, which was drawn using the total sampling technique. To find out the ability of pupils in studying tree diagrams, the researcher presented a test as an instrument. To ascertain the test outcomes, the researcher employed statistical analysis for data analysis. With an average score of 78.19, the test results demonstrated that third semester students in the English Study Program at Indragiri Islamic University were enough in understanding tree diagrams. The researcher came to the conclusion that there is room for improvement in the third semester English Study Program students at Indragiri Islamic University proficiency with tree diagrams.